Biblical hermeneutics as the structuralist of the poetics of "The Word of Law and Grace" of Ilarion - Левченко, Наталія Микитівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article states that, for the purpose of interpreting the Biblical topos of the Law and Grace, Hilarion refers to the genre of the word.Hilarion takes first place in the title, and then in the text of the work God brings out wisdom. By law, he believes the Old Testament, which has already fulfilled its task, and Grace - the New Testament, which outlines the existence of man, his relationship with God, gives hope for eternal life.The subject of the "Word" breaks the sermon into four fragments. In the first of them, we notice the allegorical meaning of reading the Scriptures in relation to the history of mankind. The second part is devoted to the interpretation of the image of Jesus Christ, which appears as a synthesis of God and human nature. The third fragment depicts events beyond the boundary of the Bible. It is devoted to the baptism of Rus. In the fourth fragment Prince Volodymyr is glorified.Following the best traditions of Byzantine oratory prose, the author of the Word simply pours his text into quotations from the Bible and adds to them a predominantly allegorical interpretation, emphasizing that the work is not intended for proclamation, but for reading, which enabled the author to interpret the Scriptures and in the literal, and in allegorical sense.The advantage of the New Testament over the Old Testament is embodied by the author in the images of the free wife of Abraham Sarah - Grace and his servant Hagar - Law. Laconic retelling of God-inspired text, Hilarion interprets the old-czarist images, as those that represent the new covenants at the level of allusions, presented them in the form of additional parallel antithesis. The same anti-colored color is also depicted by the images of their children. Isaac was born from a free woman, which means that he represents freedom, Ishmael is from a slave, hence his image symbolizes slavery.He who receives Grace receives goodness, love, becomes the son of God, and begins to live a new life in the Holy Spirit through which the believer is through. The overcoming of the Law and the perception of Grace means, according to Hilarion, the acquisition of spiritual freedom.